Revolt on Clydeside? Space, politics and populism. (June 2015) - Featherstone, David
Abstract: This critical review contributes to debates on the geographies of politics and anti-politics through a discussion of recent political developments in Scotland. It interrogates some of the populist geographies of opposition and antagonism that have been central to the politics of the 2014 Scottish independence referendum and its aftermath. I consider the significance of such political organising for left alternatives and discourses of localism in contexts of austerity and crisis. I conclude by arguing for attention the generative spatial practices which shape politicization and depoliticisation.